The marine and estuarine shrimps of the Palaemoninae (Crustacea: Decapoda: Caridea) from Brazil - Ferreira, Rodrigo Simões; Vieira, Rony Roberto Ramos; D’incao, Fernando (Zootaxa, 2010)
This study presents the current taxonomic and distributional information of the marine and estuarine species of Palaemoninae subfamily of the Brazilian coast, totaling 13 species. It is also provided an identification key for the species.